Multiplicidade, acontecimento e modelo estratégico : um estudo sobre a analítica do poder de Michel Foucault - Rauan Chaves Fernandes (2024)
This dissertation aims to define Michel Foucault's analysis of power according to the issues involving the strategic model and the analysis of the event ("événement"). Our hypothesis is that the assumption of multiplicity adopted in the analysis of the event underlies the understanding of power in its relational and strategic character, demonstrating that it is something perspective, plural and multidimensional, which confronts the criticism of the normative deficit presented by authors such as Jürgen Habermas and Nancy Fraser, for whom his conception of power would be dualistic and one-dimensional. In the first chapter, we will define genealogy according to the knowledge-power relationship; then, based on its critical dimensions of denaturalization of the present and counter-history, followed by its definition based on the strategic model. In the second chapter, we will work on discussions of method linked to the strategic model, contrasting it with the theory of sovereignty and Marxist theories of the State and ideology, and then presenting its methodological postulates, which frame the figure of the multiplicity of force correlations. We will also deal with the complex and heterogeneous relational aspect of the web of power relations, through a description of the research into the different mechanisms of power undertaken in books and courses from the 1970s. In the third chapter, we will consider Deleuze's hypothesis that there would be a theory of multiplicity in Foucault and we will present the criticisms of Critical Theory directed to genealogy; we will verify the role of the “causal demultiplication” procedure in the analysis of the event to reflect on the problems of the insertion of philosophy in history, anti-foundationalism, nominalism and historical perspectivism, in order to respond to the objections presented; dealing, finally, with the problem of the relationship between the intelligibility of war and the intelligibility of the government.